Real‐world data on microsatellite instability status in various unresectable or metastatic solid tumors. Issue 3 (7th February 2021) - Akagi, Kiwamu; Oki, Eiji; Taniguchi, Hiroya; Nakatani, Kaname; Aoki, Daisuke; Kuwata, Takeshi; Yoshino, Takayuki
Abstract: Microsatellite instability‐high (MSI‐H) is an important biomarker for predicting the effect of immune checkpoint inhibitors (ICIs) on advanced solid tumors. Microsatellite instability‐high is detected in various cancers, but its frequency varies by cancer type and stage. Therefore, precise frequency is required to plan ICI therapy. In this study, the results of MSI tests actually carried out in clinical practice were investigated. In total, 26 469 samples of various cancers were examined between December 2018 and November 2019 to determine whether programmed cell death‐1 blockade was indicated. The results of MSI tests were obtained for 26 237 (99.1%) of these samples. The male : female ratio was 51:49 and mean age was 64.3 years. In all samples, the overall frequency of MSI‐H was 3.72%. By gender, the frequency of MSI‐H was higher in female patients (4.75%) than in male patients (2.62%; P  < .001). A comparison by age revealed that the frequency of MSI‐H was significantly higher in patients younger than 40 years of age (6.12%) and 80 years or older (5.77%) than in patients aged between 60 and 79 years (3.09%; P  < .001). Microsatellite instability‐high was detected in 30 cancer types. Common cancer types were: endometrial cancer, 16.85%; small intestinal cancer, 8.63%; gastric cancer, 6.74%; duodenal cancer, 5.60%; and colorectal cancer, 3.78%. Microsatellite instability‐high was detected in cancer derived from a wide variety of organs. The frequency of MSI‐H varied by cancer type and onset age. These data should prove especially useful when considering ICI treatment. Abstract : In this study, we presented real‐world data on microsatellite instability status in various unresectable or metastatic solid tumors to determine if pembrolizumab treatment was indicated.